UI/UX Design of a Web-Based Community Discussion Forum Application for Rumah Kreatif Wadas Kelir using User-Centered Design and User Acceptance Testing - Akmal Rafly Dzunurain; Sarah Astiti (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
Rumah Kreatif Wadas Kelir (RKWK) is a community literacy organization established in Purwokerto, Central Java. As its members and volunteers expanded across different regions, communication through social media and instant messaging became unstructured, leading to knowledge loss, ineffective coordination, and limited access to information. This study aims to design a User Interface (UI) and User Experience (UX) for a web-based discussion forum using the User-Centered Design (UCD) approach. The research followed four stages: identifying user needs through interviews and questionnaires involving 30 members, analyzing the context of use with user personas, user journey maps, and use case diagrams, developing a high-fidelity prototype in Figma, and evaluating the design through User Acceptance Testing (UAT). The prototype incorporates a mobile-first interface, community-based topic categorization, and accessibility-oriented typography. UAT evaluated interface navigation, aesthetics, topic creation, search functionality, responsiveness, and overall satisfaction. The prototype achieved an average acceptance score of 84.6%, categorized as “Very Good.” These findings indicate that the proposed UI/UX design effectively supports communication, collaboration, and knowledge sharing within the RKWK community.